A new type of environmentally friendly magnesia tailings brick and its preparation method
By using a specific proportion of magnesite tailings, silicate cement, silica fume, fly ash, reinforcement fiber and water reducer in magnesite tailings bricks, combined with the preparation method of modified silica fume and reinforcement fiber, the problem of low compressive strength of magnesite tailings bricks is solved, higher mechanical strength and durability are achieved, and thermal conductivity is reduced.
Patent Information
- Application Number
- CN202410719880.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-05
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-06-05
AI Technical Summary
The existing magnesite tailings bricks have low compressive strength, resulting in poor durability.
A new environmentally friendly magnesite tailings bricks are prepared by stirring and pressing molding, and the mechanical properties of modified magnesite tailings bricks are improved with the help of modified magnesite fume and reinforcement fibers.
It improves the mechanical strength and durability of magnesite tailings bricks, while reducing their thermal conductivity, and is suitable for thermal insulation, sound insulation and high-strength wall bricks.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a novel environmentally friendly magnesite tailings brick and a preparation method thereof. Background Art
[0002] Magnesite is a dominant mineral resource in my country, and its reserves, output and export volume rank first in the world. Magnesite (also known as magnesite, chemical formula MgCO3) belongs to the calcite carbonate mineral, which often coexists or associates with minerals such as dolomite, calcite, talc, serpentine, chlorite and quartz. Its chemical composition is mainly MgO and a small amount of impurities such as SiO2, CaO, Al2O3 and Fe2O3, which form silicon / calcium / aluminum / iron magnesite, etc. During the mining process of magnesite, about 50% of the tailings will be produced in the form of industrial solid waste. A large amount of accumulated tailings will have adverse effects on the environment and land. How to safely and efficiently handle magnesite tailings, improve the utilization efficiency of tailings, and relieve the discharge and storage pressure of tailings ponds has become the focus of research attention.
[0003] Chinese patent document CN112897955A discloses a steam-free and fire-free tailings brick and a preparation method thereof, wherein the steam-free and fire-free tailings brick is prepared from solid raw materials, admixtures and water, wherein the mass of the solid raw materials is 100%, and the solid raw materials include 55-65% of low-silicon and high-magnesium iron tailings, 14-22% of cement and the remainder of river sand; the admixture is wood calcium, and the mass of the wood calcium is 0.5% of the mass of cement; the mass of the water is 10-12% of the mass of the solid raw materials; the mass content of silicon in the low-silicon and high-magnesium iron tailings is 37-39%, and the mass content of magnesium is above 30%. The present invention utilizes low-silicon and high-magnesium iron tailings to prepare double-free bricks, which has simple process, low cost, high tailings utilization rate, and the prepared double-free bricks can reach MU10 grade, but the steam-free and fire-free tailings brick has low compressive strength and is prone to poor durability. Summary of the invention
[0004] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to provide a new type of environmentally friendly magnesite tailings brick, which has higher mechanical strength and lower thermal conductivity.
[0005] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a novel environmentally friendly magnesite tailings brick, comprising the following components in parts by weight: 80-100 parts of magnesite tailings, 30-50 parts of ordinary Portland cement, 10-20 parts of silica fume, 5-15 parts of fly ash, 5-10 parts of reinforcing fiber, 0.4-1 parts of water reducer, and 20-30 parts of water.
[0007] Preferably, the ordinary Portland cement is PO42.5 ordinary Portland cement.
[0008] Preferably, the silica fume is modified silica fume, and the preparation method thereof is as follows:
[0009] After mixing silica fume, ordinary Portland cement and sodium carbonate aqueous solution evenly, add modified silicone resin polyether emulsion, stir, add fatty alcohol polyoxyethylene ether sodium sulfate, continue stirring to produce spheres, and filter to collect the spheres; after mixing fly ash and sodium carbonate aqueous solution evenly, add the spheres, stir, filter, collect solids, and calcine the solids to obtain modified silica fume.
[0010] Further preferably, the mass ratio of the silica fume, ordinary Portland cement, modified silicone resin polyether emulsion, and fatty alcohol polyoxyethylene ether sodium sulfate is 2-4: 2-3: 0.02-0.05: 0.08-0.15.
[0011] Further preferably, the mass ratio of the fly ash to the spherical objects is 2-3:6-8.
[0012] Preferably, the fly ash is Class I fly ash.
[0013] Preferably, the preparation method of the reinforcing fiber is as follows:
[0014] 1) soaking jute fiber in a hydrochloric acid aqueous solution, stirring, taking out, washing with water, drying, dispersing in anhydrous ethanol, adding aminosilane coupling agent KH-550, heating and stirring to obtain modified jute fiber;
[0015] 2) dispersing diatomaceous earth in an aqueous solution of sodium dodecyl sulfate, adding NaOH to adjust the pH value to 8-10, adding carboxymethyl chitosan, and heating for reaction; after the reaction is completed, cooling, filtering, washing until the pH value of the filtrate is neutral, and then drying to obtain chitosan-modified diatomaceous earth;
[0016] 3) adding the modified jute fiber and chitosan-modified diatomaceous earth into anhydrous ethanol, stirring and centrifuging to separate the solid matter, and drying to obtain the reinforced fiber.
[0017] Further preferably, in step 2), the mass ratio of diatomaceous earth to carboxymethyl chitosan is 4-6:2-3.
[0018] Further preferably, in step 3), the mass ratio of the modified jute fiber to the chitosan-modified diatomaceous earth is 5-10:4-6.
[0019] Preferably, the water reducer is one of naphthalene-based water reducer, fatty acid-based water reducer and polycarboxylic acid water reducer; further preferably, the water reducer is polycarboxylic acid water reducer, a powder, and the water reduction rate is 30-40%.
[0020] In a second aspect, the present invention provides a method for preparing the above-mentioned novel environmentally friendly magnesia tailings brick, comprising the following steps:
[0021] The magnesite tailings are crushed and stirred with ordinary silicate cement, silica fume, fly ash, reinforcing fiber, water reducing agent and water to obtain a mixture; the mixture is pressed into shape and then cured to obtain the environmentally friendly magnesite tailings brick.
[0022] Preferably, the particle size of the magnesite tailings after crushing is ≤3 mm.
[0023] Preferably, the pressure used for the compression molding is 5-10 MPa, and the compression time is 2-5 min.
[0024] Preferably, the curing time is 12-48 hours.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The present invention utilizes solid waste magnesite tailings, improves the utilization efficiency of magnesite tailings, realizes the comprehensive utilization of magnesite tailings, reduces the waste of resources and environmental pollution caused by large-scale stockpiling, and has potential social and economic benefits;
[0027] 2. The modified silica fume of the present invention is prepared by bonding silica fume into balls with ordinary silicate cement, and then forming some pores under the action of a foaming agent, fatty alcohol polyoxyethylene ether sodium sulfate. After calcination, the foaming agent escapes from the matrix to form a large number of holes in the spherical matrix, so that the material has better sound absorption performance. Under the coating of fly ash, the spherical silica fume has a lower water absorption rate, and its rigid core-shell structure is conducive to improving the mechanical properties of bricks;
[0028] 3. The reinforcing fiber of the present invention can improve the elastic modulus of the brick and improve its crack resistance. The preparation method is to first introduce a coupling agent with an amino structure on the surface of the jute fiber, then react the active groups on the surface of the diatomite with carboxymethyl chitosan under alkaline conditions to obtain chitosan-modified diatomite, and finally introduce the chitosan-modified diatomite into the jute fiber modified by the aminosilane coupling agent. The introduction of chitosan makes the compatibility of diatomite and jute fiber better, makes the structure of the brick more compact, further reduces its water absorption and chloride ion permeability, and is conducive to improving the mechanical strength and durability of the brick;
[0029] 4. The new environmentally friendly magnesia tailings bricks prepared by the present invention have lower thermal conductivity and higher mechanical properties, and can be used in the field of heat preservation, sound insulation, and wall bricks with higher requirements on mechanical strength. DETAILED DESCRIPTION
[0030] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The sources of some raw materials used in the present invention are as follows:
[0032] Modified silicone resin polyether emulsion, FM-550, was purchased from Shandong Moore Chemical Co., Ltd.
[0033] Silica fume, particle size is 1500 mesh, bulk density is 200-250kg / m 3 , purchased from Chengdu Keliang Building Materials Co., Ltd.
[0034] Fly ash with a particle size of 200 μm and a hardness of 2 HB was purchased from Shijiazhuang Daheng Mineral Products Processing Co., Ltd.
[0035] Diatomaceous earth, with a specific surface area of 50m 2 / g, SiO2 content is 80%, purchased from Lingshou County Hengxin Mineral Products Processing Plant.
[0036] Example 1
[0037] A method for preparing a novel environmentally friendly magnesia tailings brick comprises the following steps:
[0038] 1000g of magnesite tailings was crushed to a particle size of ≤3mm, and then stirred with 500g PO42.5 ordinary Portland cement, 200g silica fume, 150g fly ash, 100g reinforcing fiber, 10g polycarboxylic acid water reducer, and 300g water at 700rpm for 20min to obtain a mixture; the mixture was pressed at a pressure of 10MPa for 2min to obtain a brick blank, and the brick blank was moved into a curing room for curing for 48h to obtain the environmentally friendly magnesite tailings brick.
[0039] The silica fume is modified silica fume, and its preparation method is as follows:
[0040] 200g of ash, 150g of ordinary Portland cement, and 300mL of 1.5mol / L sodium carbonate aqueous solution are stirred and evenly mixed, then 1.2g of modified silicone resin polyether emulsion is added, and the mixture is stirred at room temperature for 30min. 5g of fatty alcohol polyoxyethylene ether sodium sulfate is added, and stirring is continued to produce spheres, which are collected by filtration. 150g of fly ash is mixed evenly with 150mL of 1.5mol / L sodium carbonate aqueous solution, then 350g of spheres are added, stirred, filtered, and solids are collected. The solids are calcined at 500°C for 2h to obtain modified silica ash.
[0041] The preparation method of the reinforcing fiber is as follows:
[0042] 1) Soak 250g of jute fiber in a 2mol / L hydrochloric acid aqueous solution, stir for 30-60min, take out, wash with water until the filtrate is neutral, dry and disperse in 1000mL of anhydrous ethanol, add 60g of aminosilane coupling agent KH-550, heat and stir at 50°C for 1h to obtain modified jute fiber;
[0043] 2) dispersing 300 g of diatomaceous earth in 1000 mL of sodium dodecyl sulfate aqueous solution, adding 3 mol / L NaOH aqueous solution to adjust the pH value to 10, adding 150 g of carboxymethyl chitosan, and heating at 60° C. for reaction for 2 h; after the reaction is completed, cooling, filtering, washing until the pH value of the filtrate is neutral, and then drying to obtain chitosan-modified diatomaceous earth;
[0044] 3) 200 g of modified jute fiber and 120 g of chitosan-modified diatomaceous earth were added to 2000 mL of anhydrous ethanol, stirred at 750 rpm for 2 h, and then centrifuged to separate the solid matter, which was then dried to obtain the reinforced fiber.
[0045] Example 2
[0046] A method for preparing a novel environmentally friendly magnesia tailings brick comprises the following steps:
[0047] 1000g of magnesite tailings was crushed to a particle size of ≤3mm, and then stirred with 500g PO42.5 ordinary Portland cement, 200g silica fume, 150g fly ash, 100g reinforcing fiber, 10g polycarboxylic acid water reducer, and 300g water at 700rpm for 20min to obtain a mixture; the mixture was pressed at a pressure of 10MPa for 2min to obtain a brick blank, and the brick blank was moved into a curing room for curing for 48h to obtain the environmentally friendly magnesite tailings brick.
[0048] The silica ash is porous spherical silica ash coated with fly ash, and the preparation method thereof is as follows:
[0049] 200g of ash, 150g of ordinary Portland cement, and 300mL of 1.5mol / L sodium carbonate aqueous solution are stirred and evenly mixed, then 1.2g of modified silicone resin polyether emulsion is added, and the mixture is stirred at room temperature for 30min. 5g of fatty alcohol polyoxyethylene ether sodium sulfate is added, and stirring is continued to produce spheres, which are collected by filtration. 150g of fly ash is mixed evenly with 150mL of 1.5mol / L sodium carbonate aqueous solution, then 350g of spheres are added, stirred, filtered, and solids are collected. The solids are calcined at 500°C for 2h to obtain modified silica ash.
[0050] Example 3
[0051] A method for preparing a novel environmentally friendly magnesia tailings brick comprises the following steps:
[0052] 1000g of magnesite tailings was crushed to a particle size of ≤3mm, and then stirred with 500g PO42.5 ordinary Portland cement, 200g silica fume, 150g fly ash, 100g reinforcing fiber, 10g polycarboxylic acid water reducer, and 300g water at 700rpm for 20min to obtain a mixture; the mixture was pressed at a pressure of 10MPa for 2min to obtain a brick blank, and the brick blank was moved into a curing room for curing for 48h to obtain the environmentally friendly magnesite tailings brick.
[0053] The preparation method of the reinforcing fiber is as follows:
[0054] 1) Soak 250g of jute fiber in a 2mol / L hydrochloric acid aqueous solution, stir for 30-60min, take out, wash with water until the filtrate is neutral, dry and disperse in 1000mL of anhydrous ethanol, add 60g of aminosilane coupling agent KH-550, heat and stir at 50°C for 1h to obtain modified jute fiber;
[0055] 2) dispersing 300 g of diatomaceous earth in 1000 mL of sodium dodecyl sulfate aqueous solution, adding 3 mol / L NaOH aqueous solution to adjust the pH value to 10, adding 150 g of carboxymethyl chitosan, and heating at 60° C. for reaction for 2 h; after the reaction is completed, cooling, filtering, washing until the pH value of the filtrate is neutral, and then drying to obtain chitosan-modified diatomaceous earth;
[0056] 3) 200 g of modified jute fiber and 120 g of chitosan-modified diatomaceous earth were added to 2000 mL of anhydrous ethanol, stirred at 750 rpm for 2 h, and then centrifuged to separate the solid matter, which was then dried to obtain the reinforced fiber.
[0057] Comparative Example 1
[0058] A method for preparing a novel environmentally friendly magnesia tailings brick comprises the following steps:
[0059] 1000g of magnesite tailings was crushed to a particle size of ≤3mm, and then stirred with 500g PO42.5 ordinary Portland cement, 200g silica fume, 150g fly ash, 100g jute fiber, 10g polycarboxylic acid water reducer, and 300g water at 700rpm for 20min to obtain a mixture; the mixture was pressed at a pressure of 10MPa for 2min to obtain a brick blank, and the brick blank was moved into a curing room for curing for 48h to obtain the environmentally friendly magnesite tailings brick.
[0060] Comparative Example 2
[0061] A method for preparing a novel environmentally friendly magnesia tailings brick comprises the following steps:
[0062] 1000g of magnesite tailings was crushed to a particle size of ≤3mm, and then stirred with 500g PO42.5 ordinary Portland cement, 200g modified silica fume, 150g fly ash, 100g reinforcing fiber, 10g polycarboxylic acid water reducer, and 300g water at 700rpm for 20min to obtain a mixture; the mixture was pressed at a pressure of 10MPa for 2min to obtain a brick blank, and the brick blank was moved into a curing room for curing for 48h to obtain the environmentally friendly magnesite tailings brick.
[0063] 200 g of ash, 150 g of ordinary Portland cement, and 300 mL of 1.5 mol / L sodium carbonate aqueous solution were stirred and evenly mixed, followed by 1.2 g of modified silicone resin polyether emulsion. The mixture was stirred at room temperature for 30 min, and 5 g of sodium fatty alcohol polyoxyethylene ether sulfate was added. The stirring was continued to produce spheres, which were collected by filtration. The spheres were calcined at 500°C for 2 h to obtain modified silica ash.
[0064] Comparative Example 3
[0065] A method for preparing a novel environmentally friendly magnesia tailings brick comprises the following steps:
[0066] 1000g of magnesite tailings was crushed to a particle size of ≤3mm, and then stirred with 500g PO42.5 ordinary Portland cement, 200g silica fume, 150g fly ash, 100g reinforcing fiber, 10g polycarboxylic acid water reducer, and 300g water at 700rpm for 20min to obtain a mixture; the mixture was pressed at a pressure of 10MPa for 2min to obtain a brick blank, and the brick blank was moved into a curing room for curing for 48h to obtain the environmentally friendly magnesite tailings brick.
[0067] The preparation method of the reinforcing fiber is as follows:
[0068] 1) Soak 250g of jute fiber in a 2mol / L hydrochloric acid aqueous solution, stir for 30-60min, take out, wash with water until the filtrate is neutral, dry and disperse in 1000mL of anhydrous ethanol, add 60g of aminosilane coupling agent KH-550, heat and stir at 50°C for 1h to obtain modified jute fiber;
[0069] 2) Disperse 200 g of modified jute fiber in anhydrous ethanol, add 60 g of silane coupling agent, and stir at 40° C. for 3 h; add 120 g of diatomaceous earth, stir for 30 min, and centrifuge at 2000 rpm for 10 min to separate the solid matter, and dry to obtain the reinforced fiber.
[0070] Test Case
[0071] Determination of thermal conductivity: The test objects are the environmentally friendly magnesia tailings bricks prepared in Examples 1-3 and Comparative Examples 1-3, and the thermal conductivity is tested using YB / T4130-2005 "Test Method for Thermal Conductivity of Refractory Materials". The test results are shown in Table 1:
[0072] Table 1 Test results of thermal conductivity of environmentally friendly magnesia tailings bricks
[0073] <![CDATA[Thermal conductivity (W / m 2 ·K)]]> Example 1 0.131 Example 2 0.143 Example 3 0.148 Comparative Example 1 0.189 Comparative Example 2 0.165 Comparative Example 3 0.173
[0074] Determination of compressive strength: The compressive strength of the environmentally friendly magnesia tailings bricks obtained in Examples 1-3 and Comparative Examples 1-3 was measured according to the non-sintered brick test method in GB / T2542-2012 "Test Methods for Wall Bricks". Six parallel tests were conducted on each group of samples, and the average value was taken as the final test result. The test results are shown in Table 2:
[0075] Table 2 Compressive strength test results of environmentally friendly magnesia tailings bricks
[0076] Compressive strength(MPa) Example 1 28.4 Example 2 26.2 Example 3 25.8 Comparative Example 1 16.7 Comparative Example 2 21.6 Comparative Example 3 20.4
[0077] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.
[0078] The above embodiments are only preferred technical solutions of the present invention and should not be regarded as limiting the present invention. The protection scope of the present invention shall be the technical solutions recorded in the claims, including equivalent replacement solutions of the technical features in the technical solutions recorded in the claims. That is, equivalent replacement improvements within this scope are also within the protection scope of the present invention.
Claims
1. A new type of environmentally friendly magnesia tailings brick, characterized in that: The invention comprises the following components by weight: 80-100 parts of magnesite tailings, 30-50 parts of ordinary Portland cement, 10-20 parts of silica fume, 5-15 parts of fly ash, 5-10 parts of reinforcing fiber, 0.4-1 parts of water reducing agent and 20-30 parts of water; The preparation method of the reinforcing fiber is as follows: 1) soaking jute fiber in a hydrochloric acid aqueous solution, stirring, taking out, washing with water, drying, dispersing in anhydrous ethanol, adding aminosilane coupling agent KH-550, heating and stirring to obtain modified jute fiber; 2) dispersing diatomaceous earth in an aqueous solution of sodium dodecyl sulfate, adding NaOH to adjust the pH value to 8-10, adding carboxymethyl chitosan, and heating for reaction; after the reaction is completed, cooling, filtering, washing until the pH value of the filtrate is neutral, and then drying to obtain chitosan-modified diatomaceous earth; 3) adding the modified jute fiber and chitosan-modified diatomaceous earth into anhydrous ethanol, stirring and centrifuging to separate the solid matter, and drying to obtain the reinforced fiber; In the step 2), the mass ratio of diatomaceous earth to carboxymethyl chitosan is 4-6:2-3; In the step 3), the mass ratio of the modified jute fiber to the chitosan-modified diatomaceous earth is 5-10:4-6.
2. The new environmentally friendly magnesia tailings brick according to claim 1 is characterized in that: The silica fume is modified silica fume, and its preparation method is as follows: After mixing silica fume, ordinary Portland cement and sodium carbonate aqueous solution evenly, add modified silicone resin polyether emulsion, stir, add fatty alcohol polyoxyethylene ether sodium sulfate, continue stirring to produce spheres, and filter to collect the spheres; after mixing fly ash and sodium carbonate aqueous solution evenly, add the spheres, stir, filter, collect solids, and calcine the solids to obtain modified silica fume.
3. The new environmentally friendly magnesia tailings brick according to claim 2 is characterized by: The mass ratio of the silica fume, ordinary silicate cement, modified silicone resin polyether emulsion and fatty alcohol polyoxyethylene ether sodium sulfate is 2-4: 2-3: 0.02-0.05: 0.08-0.
15.
4. The new environmentally friendly magnesia tailings brick according to claim 2 is characterized by: The mass ratio of the fly ash to the spherical object is 2-3:6-8.
5. A method for preparing the new environmentally friendly magnesite tailings brick according to any one of claims 1 to 4, characterized in that: The steps include: The magnesite tailings are crushed and stirred with ordinary silicate cement, silica fume, fly ash, reinforcing fiber, water reducing agent and water to obtain a mixture; the mixture is pressed into shape and then cured to obtain the environmentally friendly magnesite tailings brick.
6. The preparation method according to claim 5, characterized in that: The particle size of the magnesite tailings after crushing is ≤3mm.
7. The preparation method according to claim 5, characterized in that: The pressure used for the compression molding is 5-10 MPa, and the compression time is 2-5 min.
Citation Information
Patent Citations
Non-autoclaved and non-fired tailing brick and preparation method thereof
CN112897955A